2022
DOI: 10.1002/cplu.202200250
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Evaluation of Neomycin‐Imidazole Conjugates for RNA Cleavage

Abstract: Targeting RNA with synthetic small molecules attracted much interest during recent years as a particularly promising therapeutic approach in a large number of pathologies spanning from genetic disorders, cancers as well as bacterial and viral infections. In this work, we took advantage of a known RNA binder, neomycin, to prepare neomycin-imidazole conjugates mimicking the active site of ribonuclease enzymes able to induce a site-specific cleavage of HIV-1 TAR RNA in physiological conditions. These new conjugat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Consistently, a study using the aminoglycoside antibiotic neomycin, coupled with an amino acid histidine, demonstrated RNA degradation capability under physiological conditions. 145 Using the PINAD methodology, two RNA degrader classes targeting unique SARS-CoV-2 genome structures were formulated against G-quadruplexes and betacoronaviral pseudoknots. 143 Their efficacy in degrading targets was validated through in vitro , in cellulo , and in vivo SARS-CoV-2 models.…”
Section: Rna Degradersmentioning
confidence: 99%
“…Consistently, a study using the aminoglycoside antibiotic neomycin, coupled with an amino acid histidine, demonstrated RNA degradation capability under physiological conditions. 145 Using the PINAD methodology, two RNA degrader classes targeting unique SARS-CoV-2 genome structures were formulated against G-quadruplexes and betacoronaviral pseudoknots. 143 Their efficacy in degrading targets was validated through in vitro , in cellulo , and in vivo SARS-CoV-2 models.…”
Section: Rna Degradersmentioning
confidence: 99%
“…Recently, a biphenyl RNase L activator identified via screening of a DNA-encoded library was used in building the dovitinib-RIBOTAC 7 that degraded miR-21 and deactivated a miR-21 -mediated cancer circuit in MDA-MB-231 cells . Apart from RNase L recruiters, bifunctional molecules with a chemical degrader of RNA including imidazole or a bleomycin derivative were developed. …”
Section: Bifunctional Molecules Targeting Rnasesmentioning
confidence: 99%
“…7 The Duca group has recently reported a similar approach, in which they weaponized the aminoglycoside antibiotic neomycin with an amino acid histidine. 8 For our studies, we developed two series of PINADs using imidazole warheads conjugated to flexible PEG chains, targeting two different structural elements of the genome of SARS-CoV-2, and demonstrated that these molecules are active using in vitro, in cellulo, and in vivo infection models of SARS-CoV-2 (Figure 1b,c).…”
Section: ■ Introductionmentioning
confidence: 99%